PENGARUH PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Muhammad Akbar. M Muhammad Akbar. M; Usman Mulbar; Rosmala Dewi (Jurnal Education, 2025)
The Teaching at The Right Level (TaRL) approach has been identified as an innovative method to improve students' mathematics learning outcomes. This study aims to analyze the impact of implementing TaRL on the mathematics learning outcomes of Grade IX students at SMP Negeri 3 Makassar, specifically on the topic of root forms. The study employed a Classroom Action Research (CAR) design based on the Kemmis-McTaggart spiral model, conducted in two cycles. The results show a significant increase in the percentage of students achieving mastery, from 21.7% in the pre-cycle phase to 56.5% in the first cycle and reaching 82.6% in the second cycle. The TaRL approach proved effective in providing personalized learning tailored to individual students' abilities, creating more meaningful learning experiences. This study contributes significantly to the development of innovative teaching strategies that address the diverse needs of students, particularly in mathematics education.